Voltage Compensation In Wind Power System Using STATCOM Controlled By Soft Computing Techniques - Bineeta Mukhopadhyay; Rajib Kumar Mandal; Girish Kumar Choudhary (Institute of Advanced Engineering and Science, 2017)
When severe voltage sags occur in weak power systems associated with grid-connected wind farms employing doubly fed induction generators, voltage instability occurs which may lead to forced disconnection of wind turbine. Shunt flexible AC transmission system devices like static synchronous compensator (STATCOM) may be harnessed to provide voltage support by dynamic injection of reactive power. In this work, the STATCOM provided voltage compensation at the point of common coupling in five test cases, namely, simultaneous occurrence of step change (drop) in wind speed and dip in grid voltage, single line to ground, line to line, double line to ground faults and sudden increment in load by more than a thousand times. Three techniques were employed to control the STATCOM, namely, fuzzy logic, particle swarm optimization and a combination of both. A performance comparison was made among the three soft computing techniques used to control the STATCOM on the basis of the amount of voltage compensation offered at the point of common coupling. The simulations were done with the help of SimPowerSystems available with MATLAB / SIMULINK and the results validated that the STATCOM controlled by all the three techniques offered voltage compensation in all the cases considered.